2018
DOI: 10.3389/fphar.2018.01000
|View full text |Cite|
|
Sign up to set email alerts
|

The NaV1.7 Channel Subtype as an Antinociceptive Target for Spider Toxins in Adult Dorsal Root Ganglia Neurons

Abstract: Although necessary for human survival, pain may sometimes become pathologic if long-lasting and associated with alterations in its signaling pathway. Opioid painkillers are officially used to treat moderate to severe, and even mild, pain. However, the consequent strong and not so rare complications that occur, including addiction and overdose, combined with pain management costs, remain an important societal and economic concern. In this context, animal venom toxins represent an original source of antinocicept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 209 publications
(268 reference statements)
1
33
0
Order By: Relevance
“…By sequence alignment, we found that the sequence of HpTx3 has high identity with those of some Nav channel peptide toxins in the NaSpTx family 3 [7,18] (see Discussion), which suggested HPLC chromatogram and the same molecular weight, the component we purified from the Heteropoda venatoria venom was identified as peptide neurotoxin HpTx3.…”
Section: Effects Of Hptx3 On Nav Channel Subtypesmentioning
confidence: 84%
See 4 more Smart Citations
“…By sequence alignment, we found that the sequence of HpTx3 has high identity with those of some Nav channel peptide toxins in the NaSpTx family 3 [7,18] (see Discussion), which suggested HPLC chromatogram and the same molecular weight, the component we purified from the Heteropoda venatoria venom was identified as peptide neurotoxin HpTx3.…”
Section: Effects Of Hptx3 On Nav Channel Subtypesmentioning
confidence: 84%
“…By sequence alignment, we found that the sequence of HpTx3 has high identity with those of some Na v channel peptide toxins in the NaSpTx family 3 [7,18] (see Discussion), which suggested that HpTx3 might have an inhibitory effect on Na v channels. In order to investigate the Na v channel-targeted activity and the subtype selectivity of HpTx3, the effects of HpTx3 on mammal Na v 1.2-1.9 expressed in HEK293T or ND7/23 cells were detected.…”
Section: Effects Of Hptx3 On Na V Channel Subtypesmentioning
confidence: 86%
See 3 more Smart Citations